Rare cases of primarily infected kidney graft transplantation with the development of purulent complications - N. V. Shmarina; K. E. Lazareva; I. V. Dmitriev; A. G. Balkarov; D. V. Lonshakov; N. S. Zhuravel; V. V. Smirnova (Трансплантология (Москва))
Background. Unexpected transmission of an infectious disease agent with a kidney graft to a recipient is a rare event but it is associated with significant morbidity and mortality, especially when exposed to multidrug-resistant bacteria that have not been eliminated by standard antibiotic prophylaxis.Objective. To demonstrate the need for immediate removal of a primary infected kidney graft in the event of local purulent complications due to the rapid development of sepsis in immunocompromised patients.Results. The paper describes a clinical course of the infectious process in two kidney recipients each of whom underwent transplantation of a primary infected graft from a single donor, taking into consideration the transplantectomy timing and the treatment outcomes.Conclusion. The Case Report shows the need for immediate transplantectomy in a kidney graft recipient when local purulent complications are detected with confirmed primary infection of the graft due to a high risk of the rapid development of sepsis and threat to life.